Synthesis of 1,3-Benzenedicarbonyl Thiourea Derivatives under Phase Transfer Catalysis - WEI, W.; CAO, C.; ZHANG, Y.M.; WEI, TAIBAO (Asian Journal of Chemistry, 2010)
A series of 1,3-benzenedicarbonyl thiourea derivatives have been prepared in good to excellent yield under the conditions of solvent-free ground and phase transfer catalysis using polyethylene glycol-400 (PEG-400) as the catalyst at room temperature. The method has advantages of easy operations, good yields, mild reaction conditions and purification and environmental acceptability.